Hydrolysis of phosphatidylcholine is stimulated by Ras proteins during mitogenic signal transduction. - Cai, H (1992)
We have used a dominant inhibitory ras mutant (Ha-ras Asn-17) to investigate the relationship of Ras proteins to hydrolysis of phosphatidylcholine (PC) in the transduction of mitogenic signals. Expression of Ha-Ras Asn-17 inhibited NIH 3T3 cell proliferation induced by polypeptide growth factors or phorbol esters. In contrast, the mitogenic activity of PC-specific phospholipase C (PC-PLC) was not inhibited by Ha-Ras Asn-17 expression. Similarly, cotransfection with a cloned PC-PLC gene bypassed the block to NIH 3T3 cell proliferation resulting from expression of the inhibitory ras mutant. Hydrolysis of PC can therefore induce cell proliferation in the absence of normal Ras activity, suggesting that PC-derived second messengers may act downstream of Ras in mitogenic signal transduction. This was substantiated by the finding that Ha-Ras Asn-17 expression inhibited growth factor-stimulated hydrolysis of PC. Taken together, these results indicate that PC hydrolysis is a target of Ras during the transduction of growth factor-initiated mitogenic signals.